Quantitative myocardial tissue characterization by cardiac magnetic resonance in heart transplant patients with suspected cardiac rejection. Issue 10 (25th September 2019) - Miller, Robert J. H.; Thomson, Louise; Levine, Ryan; Dimbil, Sadia J.; Patel, Jignesh; Kobashigawa, Jon A.; Kransdorf, Evan; Li, Debiao; Berman, Daniel S.; Tamarappoo, Balaji
Abstract: Distinct histopathologic changes occur in acute cellular rejection (ACR), antibody‐mediated rejection (AMR), and biopsy‐negative rejection (BNR). Cardiovascular magnetic resonance (CMR)‐based myocardial tissue characterization can be used to quantify these changes. We assessed T1, T2, and extracellular volume fraction (ECV) by CMR in patients with subtypes of rejection. T1, T2, and ECV were quantified at the mid‐ventricular level and compared between patients with and without rejection. The association between quantitative tissue characteristics and the combined outcome of death, retransplantation, heart failure hospitalization, or myocardial infarction was evaluated with a Cox‐proportional hazards model. In 46 patients, mean age 53.3 ± 13.7 years, 71.7% male, at a median of 7.4 years from transplant, average myocardial T1 was increased in BNR compared with no rejection (1057 vs 1012 msec, P = .006). Average myocardial T2 was elevated in all types of rejection, P < .05. In a cox‐proportional hazards model, higher T2 values were associated with an increase in the combined clinical outcome (adjusted HR 1.21, 95% CI 1.06‐1.37, P = .004) after adjusting for left ventricular mass index. Myocardial tissue characteristics are abnormal in all subtypes of rejection, and abnormal T2 quantified by CMR provides additional prognostic value.